[Memo to Samuel D Chilcote, Jr. from Walter Woodson regarding National Tobacco Council projects] - WALTER N. WOODSON (Tufts Archival Research Center, 2007)
Marginalia; Memo to Samuel D Chilcote, Jr. from Walter Woodson regarding National Tobacco Council projects. Discusses attached "Enough is Enough" piece asking tobacco farmers to stand up and fight smoking restrictions and cigarette taxes. Discusses distribution of piece in Agri-Direct and plans to send representatives to meet with farmers.